Analysis Of Tax Expenditure In The Exemption Of Taxes On Vehicular Ownership: Case Study Of Santa Elena, 2021 - Wasbrum Tinoco, Wendy; Arellano Montalvan, Esteban; Wasbrum Tinoco, Wilfrido (Revista Universidad de Guayaquil, 2022)
This work shows how the IPVM in Ecuador has changed since the tax reform law in 2010, and the creation of IACV the next year; the public administration happens to earn from a few thousands of dollars to millions of dollars in vehicle property taxes. This work provides an ex-post analysis of the tax expenditures generated by the IPVM, that previously identified those taxes benefits are really taxed expenditures, comparing with the public politics that are pursued by each tax benefit according to the PNBV, allowing to measure the fiscal cost of estimated tax expenditures, establishing the applied approach to develop these estimates, the analysis is performed separately to ease the analysis of the tax expenditures and indicate a better way to indicate their role in the tax system providing detailed information of each one. Finally, the analysis presented in this work quantifies the amount of tax expenditure caused by tax concessions pursuing public policy objectives belongings to IPVM, which is produced in Santa Elena province.
Keywords: Tax Expenditure; Tax Incentives; Public Policy; Fiscal Cost; tax exemption